O ensino de ciências na educação de pessoas jovens e adultas: análise das práticas pedagógicas desenvolvidas nos anos finais do ensino fundamental - Silvestre, David Antonio Palla (2025)
This research included the identification and analysis of the relationship between pedagogical practices and the learning of students in youth and adult education, considering science teaching in the final years of elementary school. In this way, theoretical references were used to foundation the areas of the present research, as the young and adult education, dialogical learning, dialogical society, successful educational practices, pedagogical practices and science teaching models. Regarding the methodology, the Preferred Reporting Items for Systematic Review and Meta-Analysis 2020 (PRISMA) were used to develop a systematic review and data collection was carried out in CAPES and Scopus Journals between 2018 and 2023. To analyse the 12 articles selected by the inclusion and exclusion criterias, the content analysis has used and selected four categories a priori. Regarding the results, it was possible to identify an excessive presence of the subjectivist conception in the articles, guiding pedagogical practices and, therefore, not contributing to the learning of scientific knowledge by all subjects. However, some limitations of these practices and the search, even if not declared, for practices closer to the dialogical society are evident, since those used by the constructivist model are no longer sufficient to achieve successful results in the learning of all students. At the end of the analysis, guidelines were outlined for the initial and continuing training of teachers, since updating the epistemological and methodological bases is a way of enriching education with the scientific advances that researchers have synthesized about it.